Risk factors for sporadic ovarian cancer - M. M. Vysotsky; M. A. Digayeva (Опухоли женской репродуктивной системы)
The review of the literature on the problems of sporadic ovarian cancer details the present views of its disputable risk factors, such as dietary habits, body weight, contraception, and labor, and age of commencing a sexual activity. It discusses the dietary and sexual behavior model that has changed since the Neolithic, as well as the number of menses and ovulations throughout the reproductive peri- od. The works by authors dealing with the impact of smoking and alcohol consumption on the risk of ovarian cancer are analyzed.